Eco-friendly and recyclable all cellulose triboelectric nanogenerator and self-powered interactive interface. (November 2021) - Zhang, Jintao; Hu, Sanming; Shi, Zhijun; Wang, Yifei; Lei, Yanqiang; Han, Jing; Xiong, Yao; Sun, Jia; Zheng, Li; Sun, Qijun; Yang, Guang; Wang, Zhong Lin
Abstract: Environment issues calls for eco-friendly, recyclable, and biodegradable natural materials for the extensive application of distributed energy harvesting triboelectric nanogenerators (TENGs) and wearable self-powered interfaces. Biocompatible bacterial cellulose (BC) with high crystallinity, good mechanical properties and distinctive porous network is ready to construct biodegradable and eco-friendly TENGs. Here, we develop an eco-friendly and recyclable all-cellulose energy-harvesting and interactive device based on sandwich-structured BC-TENG. It is composed of pure BC and conductive BC precipitated with conducting and reinforced nanomaterials as friction layers and electrodes, respectively. Degradation experiments are conducted in this work to demonstrate the active materials can be completely degraded within 8 h under the condition of cellulolytic enzyme. We have also carefully investigated the output performances of the prepared all-cellulose TENG, which shows a maximum open-circuit voltage of 29 V, short-circuit current of 0.6 μA, and output power at 3 μW. The all-cellulose TENG is readily utilized to power commercial electronics and functionalize as a wearable sewing interface to control an electronic piano. This work provides an efficient route to preparing all-cellulose energy-harvesting and interactive device with good biodegradability, which is of great importance in eco-friendly electronics, bio-adaptive human-machine interfaces and intelligent biomimetic functional devices. Graphical Abstract: ga1 We develop an eco-friendly and recyclable all-cellulose energy-harvesting and interactive device based on sandwich-structured BC-TENG. The all-cellulose TENG is readily utilized to power commercial electronics and functionalize as a wearable sewing interface to control an electronic piano. Highlights: We develop a biodegradable all-cellulose energy-harvesting and interactive device based on a BC-CNT-PPy/BC/BC-CNT-PPy sandwich-structured TENG. The biodegradation experiments are conducted to demonstrate that BC and BC-CNT-PPy membranes can be completely degraded within 8 h under the condition of cellulolytic enzyme. We systematically investigate the output performance of the all-cellulose TENG. It is successfully used to power commercial electronic devices and functionalize as an interactive interface.